2008
DOI: 10.4049/jimmunol.180.3.1954
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment of Animal Models of Rheumatoid Arthritis with Small-Molecule Cyclin-Dependent Kinase Inhibitors

Abstract: Intraarticular gene transfer of cyclin-dependent kinase (CDK) inhibitors to suppress synovial cell cycling has shown efficacy in treating animal models of rheumatoid arthritis. Endogenous CDK inhibitors also modulate immune function via a CDK-independent pathway. Accordingly, systemic administration of small molecules that inhibit CDK may or may not ameliorate arthritis. To address this issue, alvocidib (flavopiridol), known to be tolerated clinically for treating cancers, and a newly synthesized CDK4/6-select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
72
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 90 publications
(81 citation statements)
references
References 34 publications
4
72
0
1
Order By: Relevance
“…In our search for anticancer therapeutics, we have found that P2281 inhibits mTOR activity in colon cancer cells and suppresses DSS-induced colitis. Given that prior studies have demonstrated that compounds with anticancer activity show promising anti-inflammatory efficacy (39,43,51,59), the findings from this study, thus, reinforce the cross-therapeutic functionality of potential drugs.…”
Section: Discussionsupporting
confidence: 50%
“…In our search for anticancer therapeutics, we have found that P2281 inhibits mTOR activity in colon cancer cells and suppresses DSS-induced colitis. Given that prior studies have demonstrated that compounds with anticancer activity show promising anti-inflammatory efficacy (39,43,51,59), the findings from this study, thus, reinforce the cross-therapeutic functionality of potential drugs.…”
Section: Discussionsupporting
confidence: 50%
“…Before sacrificing, arthritis in each limb of CII-treated mice was clinically assessed by visual edema scoring from 0 to 3, as follows: 0, no swelling; 1, detectable swelling in one joint; 2, nonsevere swelling in two or more joints; 3, severe swelling in two or more joints (19). The left hind limbs, including paws and ankles, were dissected, fixed immediately for 12 h in 10% neutralizing formaldehyde, decalcified in Calci-Clear Rapid (National Diagnostics) for 12 h, and embedded in paraffin.…”
Section: Assessment Of Arthritismentioning
confidence: 99%
“…Comparable therapeutic effects were observed when the small-molecule (sm)CDKI was administered orally or i.p. (7). A separate series of our experiments disclosed that cell-cycle progression is not the only function of CDK (8).…”
mentioning
confidence: 99%